Mechanisms to identify and study the demand for innovation skills in world-renowned organizations - Cobo, C (Emerald Group Publishing Limited, 2013)
Purpose – This paper aims to explore the interrelationship between the fields of education and workforce in the context of post-industrial societies. It seeks to analyze key challenges associated with the match (and mismatch) of skill supply and demand between education and the work force. Design/methodology/approach – Using a “purposeful sample”, the study provides an evidence-based analysis that explores how and to what extent soft skills are currently required by world recognized organizations such as Greenpeace, World Bank, OECD, Google, Apple and Samsung. Findings – After a revision of different perspectives to identify and categorize the key skills of the twenty-first century, the study describes seven non-technical cognitive and social key skills called soft skills for innovation. Research limitations/implications – After exploring a small sample size of five recent job vacancies promoted by six major international organizations, the study analyzes the current demand for soft skills for innovation such as, collaboration, critical thinking, contextual learning, searching, synthesizing and disseminating information, communication, self-direction and creativity. The methodology adopted and the data retrieval process can be replicated with either a larger sample or more focused workforce sectors. Practical implications – The described “skills mismatch” emphasizes the importance of creating different strategies and tools that facilitate the recognition of skills acquired independently of educational contexts. Social implications – This study contributes to the current and ongoing discussions regarding relevant key soft skills for graduates and future employees providing an updated idea of skills demanded by world class organizations. Originality/value – The paper provides evidence-based information (data available online) that can contribute to rethinking curriculums and exploring “blended” models that mix real life and teaching contexts stimulating the development of soft skills for innovation.